Current Problems in the Use of Illegal Substances Ingredients - Türkmen, Zeynep (The Bulletin of Legal Medicine, 2014)
It is known that many diluents and adulterants are used to make illegal substances appear in larger amount and bring more profit. Identification of such additives in illegal substances is particularly important, since some of the toxic effects of such compounds are much more harmful than impact of illegal substances used. The unpredictable substances may endanger the lives of illegal substance users. In this study, the content of two samples brought with suspected illegal substance were investigated and in Sample 1, paracetamol, caffeine and griseofulvin, other the hand in Sample 2 phenacetin were determined as adulterants. Increasing of the contents and ratio of the adulterants in these illegal substances day by day, it should be considered that these additives should also be taken into account in the case of an unexpected death or permanent damage. The findings were evaluated with the groups who have done similar studies in terms of change in content of adulterants and possible health risks, which they may caused. Keywords: Illegal substances; impurities; toxic effects; adulterants